2005
DOI: 10.1097/01.rct.0000182855.98144.15
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Pseudosarcomatous Fibromyxoid Tumor

Abstract: A cardiac pseudosarcomatous fibromyxoid tumor (PFT) is described in a previously healthy 35-year-old man, together with a review of the literature. Pseudosarcomatous fibromyxoid tumor is within the spectrum of inflammatory (myofibroblastic) pseudotumors. It has previously been described predominantly within the genitourinary tract and respiratory tract. Inflammatory pseudotumor is rare as a cardiac tumor, and cardiac PFT is not previously reported. No recurrence or metastatic disease has been reported after re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Although MRI has better soft tissue characterization and superior contrast resolution than MR, advances in CT scanner technology in the last few years make CT a robust and reproducible technique for cardiac evaluation. 1 CT remains the best way to show intracardiac expansion due to tumor, and CT also has the advantage of evaluating the entire thorax, including the mediastinum, lungs, and great vessels for further metastatic disease. 5 The prognosis of these patients is not well known; however, the most favorable prognostic indicator is the complete resection of the tumor, 7 and when surgical resection is feasible, this is the indicated therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MRI has better soft tissue characterization and superior contrast resolution than MR, advances in CT scanner technology in the last few years make CT a robust and reproducible technique for cardiac evaluation. 1 CT remains the best way to show intracardiac expansion due to tumor, and CT also has the advantage of evaluating the entire thorax, including the mediastinum, lungs, and great vessels for further metastatic disease. 5 The prognosis of these patients is not well known; however, the most favorable prognostic indicator is the complete resection of the tumor, 7 and when surgical resection is feasible, this is the indicated therapy.…”
Section: Discussionmentioning
confidence: 99%
“…1 They are associated with a worse prognosis than primary cardiac tumors. In a 30-year review of cardiac neoplasms at autopsy, Butany et al 2 showed that metastases to the heart and pericardium were 132 times more common than primary cardiac neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…IMT is a rare benign tumor characterized by proliferation of myofibroblast and inflammatory cell infiltration. There have been few case reports of IMT with the exact incidence unknown .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac IPT/IMT is rare, and only isolated cases have been reported: 39 cases have been reported in the English language literature, and 37 are listed in Table 2 (the two unlisted cases lacked precise data) 3,6,10–33 . The patients ranged in age from 5 weeks to 72 years, with a predilection for females.…”
Section: Discussionmentioning
confidence: 99%